AN AXIOLOGICAL UNDERSTANDING OF THE SOCIO-HISTORICAL NEEDS AS A BASIC PRE-SUPPOSITION FOR A PROPOSAL OF SOCIAL MOBILIZATION STRATEGIES DIRECTED TO PROFESSIONALS LINKED TO ASSOCIATIONS OF PHYSICAL EDUCATION PROFESSIONALS (APEF' S) (Fiep Bulletin - online, 2014)
Throughout history, associations or associativist movements, had provided to men with alternatives so that these could surpass the most diverse difficulties found by them and, as to professsions, such movements have also positively influenced their development in different aspects, mainly, in the legal scope. However, it is observed in these entities, as well as, in the social movements in general, an apparent challenge with respect to the mobilization of people, that is, a lack of co-participation among the professionals involved with these associations. Facing such a problem, its essence, which gave origin to this study, was the difficulty that Physical Education Professionals, vinculated to APEF'S, present in implanting a performance policy with strategies of social mobilization, which contribute to, democratically, co-participate in the planning, execution and evaluation of actions that have as an objective to cater to the common and collective interests of such professional category. Thus, it was established as objective to develop an axiological understanding based only in the socio-historical aspects that involve the Professionals associated to a APEF and, from the lacks related to these, to establish strategies of social mobilization which allow, at least, to minimize the lack of co-participation of some of them in the planning, execution and evaluation of actions that must be reached and assured, democratically, in the scope of such Association. The strategies, which have been based on the implementation of "institutional events", that is, Congresses, Seminars, Symposiums, among others, from an innovative model, considering the problem of certain bonds, has demonstrated the possibility to minimize the lack of participation of the Professionals associated to APEF' S. That was so, because the innovative model aforementioned has proved itself capable of meet the needs of the professionals and constitute `value' for these professionals.
Keywords: Axiological understanding; Strategies of Social Mobilization; Associations Physical Education Professionals